Effects of traumatic birth experience and transmission intergenerational Travmatik doğum deneyiminin etkileri ve nesiller arası aktarımı - Aydın, Nihal; Yıldız, Hatice (Uluslararasi Insan Bilimleri Dergisi, 2018)
The birth is an individual and also important expression for women life. This experience can be perceived in a different way by each woman that can be defined by different feelings such as positive, negative or mixed. Some women perceive birth experience as a traumatic event. Traumatically perceived birth is considered an event that may trigger Posttraumatic Stress Disorder (PTSD) reaction. It is stated that traumatic birth experience may cause permanent or long-term negative consequences in women's life, may negatively affect future health, subsequent birth experiences and family relations. It is reported that birth is part of the continuity from past to future and the effects are not limited to the woman giving birth, but also that the subsequent generations, and even the other women around it, can influence the birth perceptions and experiences. There are many studies shows that the effects of traumatic events are transmitted to the next generation. This genetic transmission suggests that traumatic birth is a serious problem not only affecting the women who will give birth to nowadays but also having long-term consequences. From today's women to future generations, obstetrics and gynecology nurses have important responsibilities to prevent of reaching traumatic experience of birth, is a natural part of women's life. In this article, it was aimed to investigate the importance of traumatic birth concept, risk factors, existing effects and future generations in the context of literature and to draw attention to the responsibilities of the obstetrics and gynecology nurses.Extended English summary is in the end of Full Text PDF (TURKISH) file. ÖzetDoğum bireyseldir ve kadın için çok yönlü önemli bir yaşam deyimidir. Bu deneyim her bir kadın tarafından farklı algılanabilmekte, olumlu, olumsuz ya da karışık farklı duygularla tanımlanabilmektedir. Bazı kadınlar ise doğum deneyimini travmatik bir olay olarak algılayabilmektedir. Travmatik olarak algılanan doğum, Posttravmatik Stres Bozukluğu (PTSB) reaksiyonunu tetikleyebilecek bir olay olarak kabul edilmektedir. Travmatik doğum deneyiminin kadının hayatında kalıcı veya uzun vadeli olumsuz sonuçlar doğurabileceği, gelecekteki sağlığını, sonraki doğum deneyimlerini ve aile içi ilişkilerini olumsuz etkileyebileceği belirtilmektedir. Doğumun geçmişten geleceğe giden devamlılığın bir parçası olduğu belirtilmekte ve etkilerinin doğum yapan kadınla sınırlı kalmayıp, onunla birlikte çevresindeki diğer kadınların ve hatta sonraki nesillerin doğum algılarını ve deneyimlerini de etkileyebildiği bildirilmektedir. Travmatik olayların etkilerinin sonraki nesillere aktarıldığını gösteren pek çok çalışma bulunmaktadır. Bu genetik aktarım travmatik doğumun da sadece günümüzde doğum yapacak kadınları etkilemeyip daha uzun vadeli sonuçları olabilecek ciddi bir sorun olduğunu göstermektedir. Kadın hayatının doğal bir parçası olan doğum eylemini günümüz kadınlarının ve gelecek nesillerin travmatik bir deneyim olarak hatırlamalarının önlenmesinde kadın doğum hemşirelerine önemli sorumluluklar düşmektedir. Bu makalede travmatik doğum kavramı, risk faktörleri, ortaya çıkan mevcut etkileri ve gelecek nesiller açısından önemini literatür bağlamında irdelemek, konuya ve kadın doğum hemşiresinin sorumluluklarına dikkat çekmek amaçlanmıştır.
Keywords: Health; Nursing; Birth; Sağlık; Hemşirelik; Doğum; Obstetrics and Gynecology Nursing; Doğum ve Kadın Hastalıkları Hemşireliği; Birth; traumatic birth; risk factors; effects; intergenerational transfer; Doğum; travmatik doğum; risk faktörleri; etkileri; nesiller arası aktarım